2016
DOI: 10.1002/2016jc011733
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear and minor ocean tides in the Bay of Biscay from the strain tides observed by two geodetic laser strainmeters at Canfranc (Spain)

Abstract: This work presents and discusses the tidal analysis of about 2.5 years of strain data recorded by two 70 m‐long high‐resolution laser strainmeters, which are operating in the Canfranc underground laboratory (Central Pyrenees, Spain). Spectra show clear tidal peaks whose frequencies range from the diurnal band to at least 8 cycles per day; strain amplitudes (relative change in length for each strainmeter) range from few 10−12 to 10−8. The reliability of observations and corrections for local distortions are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…3) is probably of anthropic origin. As for the LSC interferometers (LAB780 and GAL16), we already demonstrated that air temperature and barometric pressure effects on strain are actually negligible on time scales of one day or shorter 28,32 .…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…3) is probably of anthropic origin. As for the LSC interferometers (LAB780 and GAL16), we already demonstrated that air temperature and barometric pressure effects on strain are actually negligible on time scales of one day or shorter 28,32 .…”
Section: Resultsmentioning
confidence: 62%
“…Φ , N 2 and M 2 at each interferometer, obtained (i) computing the theoretical tidal strain components by using the reference 3 frequency-dependent Love and Shida numbers, T FCN , and Q FCN , (ii) combining them by using reasonable local effect coefficients 24,32 , and (iii) assigning them the uncertainties we got from the tidal analysis of the real extension records. Parameters…”
Section: Strain Record Analysismentioning
confidence: 99%
“…The karst aquifer is probably very heterogeneous, but the schist unit may be considered approximately homogeneous; we expect mechanical anisotropy to be of little influence on strainmeter data because compressional forces act horizontally and schist layering is almost horizontal (Figure 1f). Moreover, as for larger-scale phenomena, tidal strain (diurnal band to at least 8 cycles per day) recorded by the two strainmeters does not evidence any anomaly attributable to mechanical heterogeneity or anisotropy (Amoruso & Crescentini, 2016). Thus, for simplicity, we assume homogeneous isotropic conditions in the whole computational domain.…”
Section: Methodsmentioning
confidence: 98%
“…Although strain noise amplitude is inversely proportional to frequency, we do not filter low frequencies out, but for easier visualization, we detrend strain data whenever we plot them. On time‐scales longer than tens of seconds and shorter than several days, the largest signal on a strain record is the Earth (body and ocean loading) tides and occasionally a large earthquake or a hydrology‐associated deformation event (e.g., Agnew, 2007); loading by nonlinear shallow‐water tides in the Bay of Biscay also gives non‐negligible deformation in the study area (Amoruso & Crescentini, 2016). Therefore, we subtract linear and nonlinear tides from the strain time series before further analysis (Amoruso & Crescentini, 2020).…”
Section: Datamentioning
confidence: 99%
“…The above signifies that a missing-values prediction method based on spectral analysis would most likely make accurate predictions for most of the data variance, but it may not account for any random irregularities, such as extreme meteorological events, other anthropogenic factors (e.g., marine traffic), or events related to earth dynamics (i.e., earthquakes and sediment dynamics). Missing value imputation methods based on the frequency domain are either using the Fourier [55][56][57] or the wavelet (e.g., in [58]) spectrum of the time series.…”
Section: Spectral Analysis With Incomplete Data: the Clean Algorithmmentioning
confidence: 99%